Intervention with individuals with autism spectrum disorder: a professional perception - Rocha, Aila Narene Dahwache Criado (2018)
For the systematization of interventions, it is essential to know the perception of the professionals who work with individuals with Autism Spectrum Disorder to instrumentalize them in the improvement actions to stimulate their skills and fully meet their needs. The objective of this study was to analyze the perception of professionals about the work done by them with the children and youth with Autism Spectrum Disorder as well as identify their intervention strategies. This study included 16 participants, twelve teachers and four health providers. To collect the data we designed semi-structured interviews in order to understand the perception of professionals about working with these individuals. After the interview can identify that professionals have practical knowledge about the features and performance with children and youth with Autism Spectrum Disorder, but need formal spaces for the exchange of experiences and the construction of new knowledge.